Finding the Career Path: Career Well-being of Vocational High School Students in Major Selection - Muhammad Rafli; Muzayyinah Al Usrah; Nusril Muchtadi (Bulletin of Social Studies and Community Development, 2024)
Abstract: This study aims to analyze how students at SMK Negeri 1 Bantaeng explore their major or career choices and how these choices relate to their future career well-being. The research employs a descriptive quantitative design. The sample consists of 198 active students from vocational high schools (SMK) in Bantaeng District, South Sulawesi, Indonesia. The scale used to assess career well-being is based on the development of Coetzee's (2021) Career Well-Being Inventory. The Career Well-Being Scale uses a Likert-type scale with response criteria ranging from 1 (strongly disagree) to 5 (strongly agree). Based on the research findings, students at SMK Negeri 1 Bantaeng demonstrate high overall career well-being, with aspects of affective career planning, career meaningfulness, and social support all falling within the high category. This reflects that students feel comfortable and supported in selecting their majors and planning their careers. The recommendations of this study include enhancing career planning support through strengthened guidance and counseling programs, as well as fostering partnerships with the industry to expand students' career networks.     Keywords: career well-being, students; career path, vocational high school.